The high prevalence of obsessive-compulsive disorder in patients with chronic pain. - Ali Mehraban (Iranian Journal of Psychiatry, 2014)
Objective: Chronic pain is a common disorder with a high prevalence of psychiatric disorder that imposes a worse prognosis on both conditions. Obsessive compulsive disorder (OCD) is estimated to be the fourth most prevalent life time psychiatric disorder, but yet has gained less attention in chronic pain comorbidity researches." Methods: Ninety three heterogeneous chronic pain patients who attended a pain clinic in Tehran (Iran) in an outpatient setting during three months were included in this study. Diagnosis was made by Structured Clinical Interview for DSM-IV (SCID).The mean age of the patients was 46.37 (SD 15.005) years; of the patients, 66.7% were female and 33.3% were male. The mean duration of pain was 34.43 (SD 51.422) months. The mean pain severity on numerical pain scale was 5.82 (SD 1.950) from 10. Results: The mean pain site number was 3.68 (SD 3.401) from the maximum of 27 places. Furthermore, 61.3% of the participants were diagnosed with lifetime OCD, 25.8% with subclinical OCD and 61.5 % with major depressive disorder (MDD). OCD diagnosis was not correlated with MDD or pain intensity. Female gender was associated with OCD (OD; 4.182, 95% CL (1.655-10.568)). Pain intensity was correlated with MDD (P < 0.05). Conclusions: The high prevalence of OCD was comorbidity, independent of MDD and most pain characteristics. The high prevalence of OCD may be explained by the high rate of undiagnosed cause of pain as well as cultural and local factors. Using screening tests is suggested for tackling under diagnosis and under treatment of OCD and MDD.